Audit of pediatric hematology-oncology outpatients in Kuala Lumpur. - Menon, Bina Sharine; Eni , Juraida; Mohd Ibrahim, Hishamshah; Mohamed, Mahfuzah; Ho, Caroline; Raja Khuzaiah, (Seameo Regional Tropical Medicine & Public Health Network, 2008)
The aims of this study were to determine the types of cancers and hematological disorders in patients attending a pediatric hematology-oncology clinic. This was a prospective study at the Pediatric Institute, General Hospital Kuala Lumpur, Malaysia from June 2005-November 2006. During the 18-month study 803 patients attended the clinic, 730 had oncological problems and 73 had hematological problems. The age range was from 2 months to 28 years (median 6 years). The patients were Malay (66%), Chinese (23%), Indian (10%) and other races (1%). Of the oncological patients, 51% had either leukemia (n=293) or lymphoma (n=77).The other most common diagnoses were retinoblastoma, followed by Wilm's tumor and germ cell tumors. Six patients (0.8%) developed a second malignant neoplasm. Of the hematological patients, 60% had platelet disorders, most commonly chronic immune thrombocytopenic purpura. Twenty-four per cent had bone marrow failure and 16% had red cell disorders.